"Valores democráticos e elaboração de conceitos : Tocqueville e Deleuze nas aulas de filosofia" - Luciano Magalhães Alves (2020)
This work aimed to present the philosophy as creative concepts in Deleuze, and from this perspective assist in the discussion of democratic values in philosophy classes. Through practical classroom experience, showing how philosophical activity would allow the constitution of critical citizens through argumentative practices. The text proposes to discuss two elements: The notion of teaching philosophy as a philosophical activity development concepts; Tocqueville's concepts of: equal conditions, the equality-freedom relationship, the tyranny of the majority, and the importance of associative life; and the argumentative processes (understood here as the different didactic situations where students are led to discuss, debate and justify their ideas) in philosophy classes. The result goals to propose a didactic sequence. The analysis and the results of this practice will be proposed as an addition to the curricular proposal for the teaching of philosophy of the Secretaria de Estado de Educação de Mato Grosso do Sul, because it does not include the authors approached. Therefore, it could guide the work of the other professionals in the same subject area. KEYWORDS: Concept elaboration. Democracy. Deleuze. Tocqueville. Argumentation